2014
DOI: 10.1016/j.apenergy.2013.11.059
|View full text |Cite
|
Sign up to set email alerts
|

Latent heat augmentation of thermocline energy storage for concentrating solar power – A system-level assessment

Abstract: Molten-salt thermocline tanks are a low-cost energy storage option for concentrating solar power plants. Despite the potential economic advantage, the capacity of thermocline tanks to store sufficient amounts of high-temperature heat is limited by the low energy density of the constituent sensible-heat storage media. A promising design modification replaces conventional rock filler inside the tank with an encapsulated phase-change material (PCM), contributing a latent heat storage mechanism to increase the ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…discharging is a major concern for LHS systems since most of the PCMs have very low thermal conductivity [2]. A number of methods have been proposed to increase the thermal conductivity of PCMs [3][4][5][6][7][8][9]. The finned tube configuration [9][10][11][12], metal structure insertion into the PCMs [13,14], and dispersion of thermally conductive nano or micro particles (graphite flakes, CNTs, graphene, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…discharging is a major concern for LHS systems since most of the PCMs have very low thermal conductivity [2]. A number of methods have been proposed to increase the thermal conductivity of PCMs [3][4][5][6][7][8][9]. The finned tube configuration [9][10][11][12], metal structure insertion into the PCMs [13,14], and dispersion of thermally conductive nano or micro particles (graphite flakes, CNTs, graphene, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…They act as a sacrificial layer which is removed by heat treatment and leads to a void space between the PCM and the shell that will allow the expansion of the PCM when melting and protect the PCM from dissolving in water as well as in several organic solvents. This route has been also found in the state of the art analysis by University of South Florida [13,14].…”
Section: Inorganic Salt Pcmmentioning
confidence: 75%
“…A recent publication [13] shows the simulation of tank with a cascaded filler structure composed of multiple encapsulated PCM with their melting temperatures tuned along the tank height. It has been concluded that modification of the porous bed with a cascaded PCM structure increases the utilization of the latent heat and can provide significant improvement over conventional quartzite rock filler.…”
Section: Thermocline Systemmentioning
confidence: 99%
“…Yang and Garimella [15] proposed a comprehensive, two-temperature model developed for the cyclic operation of a thermocline operating with a commercially available molten salt as the heat transfer fluid and quartzite rock as the filler. In order to increase the overall energy density, Fluckiger and Garimella [16] studied a promising design modification using an encapsulated phase-change material (PCM) as filler material. The utilization of latent heat can provide significant improvement over conventional quartzite rock filler.…”
Section: Introductionmentioning
confidence: 99%